Analisis Performa Kampas Rem Rekayasa Ramah Lingkungan: Peran Phenol Formaldehyde dan Aditif Biokomposit - Bustomi, Ahmad; Nur, Hamid Ramadhan; Muhammad, Rouf; Zaman, Mochamad Nuruz (Politeknik Negeri Padang, 2024)
The issue of environmental damage is increasingly becoming a concern of the global community, including in the automotive industry. The use of environmentally friendly materials and the reduction of dependence on mineral-based or synthetic materials have become challenges that need to be overcome. Brake pads, as one of the components that have a vital role in a motor vehicle, are generally made of heavy metal materials, asbestos, and synthetic resins that can pollute the environment during the production process. The use of environmentally friendly raw materials such as wood powder, cocopeat and coconut shell carbon is an alternative in the brake pad production process. This study aims to analyze the performance of brake pads made of phenol formaldehyde with the addition of environmentally friendly biocomposites in the form of wood powder, cocopeat and coconut shell carbon. The method used is an experimental laboratory designed to evaluate the friction coefficient, wear rate, and microstructure of materials through Scanning Electron Microscopy (SEM). The results of the study show that this biocomposite brake pad has good wear resistance at high temperatures, especially with the carbon content of coconut shells which helps improve thermal stability. However, the value of the friction coefficient of brake pads still does not meet the minimum standard set by the Indonesian National Standard (SNI) 09-0143-1987, which indicates that this material is not yet fully feasible for automotive applications with high friction demands. Further research is needed to optimize the composition of materials, especially in increasing the friction coefficient to match industry standards.